SAT0122 Opioid rotation with oral morphine to oral hydromorphone in rheumatologic non cancer pain: a retrospective study. (1st June 2001) - Grilo, R; Di Fazano, C Scotto; Coyral, D; Bertin, P; Bonnet, C; Treves, R
Abstract : Background: Although being a controversal debated, opioids may be an alternative therapeutic in intractable rheumatologic non-malignant pain (RNMP). Different mecanisms including receptor activity, cross over tolerance and toxic metabolits can explaine the differences in analgesic or adverse effect responses among opioids. Objectives: To determinated that rotation with oral morphine to oral hydromorphone can be useful for establishing a more advantages analgesia/toxicity relationship. Methods: We made retrospectivly 24 rotations in patients suffering from RNMP. Different criteria were assessed: dose of morphine and hydromorphone (mg/day), duration of treatment (days), evaluation of pain using a Visual Analogic Scale (VAS, cm) before and after rotation, and finally the causes of rotation. Results: 11 rotations were made for nausea and 13 for inefficacity. There is a significant statistical decrease of VAS after rotation (test of Student). Conclusion: Oral hydromorphone appeared to result in improvement of pain relief after rotation, and may provide a suitable alternative to bypass nausea. We observed an average morphine/hydromorphone ratio of 7:1, which has become the accepted standard.